Are the ‘born-frees’ always politically apathetic? social media use for campus politics by black undergraduates of North-West University, Mafikeng, South Africa (2018)
The South African post-apartheid Black youth—popularly known as the 'Born Frees'— have been stereotyped politically apathetic. But there are yet empirical studies to prove that these youth are really perpetually averse to political participation, even in their universities, especially with emergence of social media that provide digital space for social and political engagements. With the specific attention on Black students of the Mafikeng campus of North-West University, South Africa as the study population, this study, therefore, employed a sequential qual-QUANT exploratory design to explore how Black undergraduates use social media to engage in political activities in the university setting. Anchored on the Uses and Gratifications Theory, the study employed questionnaire to collect data from 232 respondents selected through stratification and convenience sampling. Majority (77.1%) of the students affirmed they actively participated in campus politics using the social media (78.0%) and text messages via mobile phones (60.7%). Ironically, only 36.2% of the students said they used direct interpersonal communication as the communication modes for political engagement. The trend established in this study challenges scholars‘ assumption that the Post-apartheid Black youth of South Africa are politically apathetic. Students‘ interest and participation in campus politics suggest that, with effective use of the digital space that is relatively free, accessible, interactive, and independent of undue control by the state apparatus, the Black youth can also contribute positively to the South African democratic project.